Azole Resistance and cyp51A Mutation of Aspergillus fumigatus in a Tertiary Referral Hospital in Taiwan - Tsun-Hao Hsu; Po-Yen Huang; Yun-Chen Fan; Pei-Lun Sun (Journal of Fungi, 2022)
Azole resistance in Aspergillus fumigatus has increasingly been reported worldwide. Its major mechanism of resistance is mediated by mutations in cyp51A. The objective of this study was to test the antifungal susceptibilities of A. fumigatus isolates from Chang Gung Memorial Hospital (CGMH), the largest tertiary referral hospital in Taiwan, and to investigate cyp51A mutations in azole-resistant strains. A. fumigatus isolates preserved in the Research Laboratory of Medical Mycology of CGMH from 2015 to 2021 were used. Antifungal susceptibility testing was performed using the YeastOneTM method. Isolates with high minimal inhibitory concentrations (MICs) against antifungals were further tested using the Clinical and Laboratory Standards Institute (CLSI) broth microdilution method. Mutations in the cyp51A in azole-resistant strains were detected by Sanger sequencing. The overall prevalence of azole-resistant isolates was 1.77% (two out of 113 isolates). The two azole-resistant strains had tandem repeats (TR) in the promoter region and mutations in the cyp51A gene (TR34/L98H and TR34/L98H/S297T/F495I). One strain showed intermediate susceptibility to voriconazole, and its Cyp51A protein had five amino acid substitutions (F46Y/M172V/N248T/D255E/E427K). TR34/L98H and TR34/L98H/S297T/F495I are the most prevalent cyp51A mutations in Taiwan, mediating azole resistance based on current publications and our results. YeastOneTM was validated as a rapid tool for the antifungal susceptibility test; however, further confirmation by CLSI should be considered when MIC values of voriconazole, posaconazole, and amphotericin B are close to the clinical breakpoints or ecological cutoff values.